Ground effect on the power extraction performance of a flapping wing biomimetic energy generator. (April 2015) - Wu, J.; Yang, S.C.; Shu, C.; Zhao, N.; Yan, W.W.
Abstract: In this study the ground effect on the power extraction by a flapping wing based biomimetic energy generator was numerically investigated. The use of flapping wings, which derives inspiration from the study of biomimetics, has been considered as an alternative approach to developing an energy generation system that is completely different from the traditional turbine-based power generation unit. A NACA0015 airfoil, which is commonly used to model the wing cross-section, was placed in a two-dimensional laminar flow system and imposed with a harmonic plunge and pitch rotary motion. To carry out numerical simulations, the immersed boundary-lattice Boltzmann method was employed. At a Reynolds number of 1100 and with the position of the airfoil pitching axis at one third of the chord length from the leading edge, the influence of the clearance between the airfoil pitching axis and the ground ( c ≤ h 0 ≤5 c, c is the chord length of the airfoil), the amplitude ( h m =0.5 c and c, α n = 10 ° and 20 ° ) and frequency (0.05≤ St ≤0.5) of motion on the force behavior and power extraction were systematically evaluated. Compared to the situation in which there was no ground effect, the airfoil placed in close proximity to the ground gave improved power extraction performance. For given amplitude, as the clearance decreased the power extraction efficiency improved. The maximum efficiency improved by 28.6%. Moreover, it was found that the contribution to efficiency improvement was essentially from the increased plunging component of the power extraction, resulting from the generation of high lift force, rather than that of pitching.